Penerapan Undang-Undang Nomor 14 Tahun 2005 Terhadap Pelaksanaan Sertifikasi Guru Di Kota Mataram - Hj. Zohriah (Jatiswara, 2016)
This study is only aimed at the implementation of the Civil Service certification for teachers in Mataram, starting from the teaching profession allowance arrangement pursuant to Law No. 14 Year 2005, Application of the Law No. 14 Year 2005 in Mataram and the various constraints in the implementation of the Law Law Number 14 Year 2005 in Mataram and proposed solutions to overcome the stretcher. The results of this study found the insinkronisasi the Government Regulation No. 41 of 2009 by the Ministry of Finance (PMK) are used as guidelines in the payment of teachers' professional allowance. It also found the vagueness of norms in Article 35 paragraph (2) of Law No. 14 Year 2005. Although Law No. 14 Year 2005 effective as expected, but there are some obstacles in the implementation of Law No. 14 Year 2005 on the city of Mataram. The solution is that the Minister of Finance to follow the provisions of the Government Regulation Number 41 Year 2009, which ordered that the payments be paid every month teacher certification. To resolve the conflict norms in Article 35 paragraph (2) of Act No. 14 of 2005 so as not to harm the teacher is required to revise Law No. 14 Year 2005 on Teachers and Lecturers, in particular Article 35 paragraph (2) in order to sync with Article 35 paragraph (1).